Red State Religion: Faith and Politics in America's Heartland - Wuthnow, Robert (Princeton University Press, 2012)
No state has voted Republican more consistently or widely or for longer than Kansas. To understand red state politics, Kansas is the place. It is also the place to understand red state religion. The Kansas Board of Education has repeatedly challenged the teaching of evolution, Kansas voters overwhelmingly passed a constitutional ban on gay marriage, the state is a hotbed of antiabortion protest--and churches have been involved in all of these efforts. Yet in 1867 suffragist Lucy Stone could plausibly proclaim that, in the cause of universal suffrage, "Kansas leads the world!" How did Kansas g